2014
DOI: 10.1096/fj.13-248641
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autotaxin delays breast tumor growth and lung metastasis in mice

Abstract: Autotaxin is a secreted enzyme that produces most extracellular lysophosphatidate, which stimulates 6 G-protein-coupled receptors. Lysophosphatidate promotes cancer cell survival, growth, migration, invasion, metastasis, and resistance to chemotherapy and radiotherapy. The present work investigated whether inhibiting autotaxin could decrease breast tumor growth and metastasis. We used a new autotaxin inhibitor (ONO-8430506; IC90=100 nM), which decreased plasma autotaxin activity by >60% and concentrations of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
162
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(177 citation statements)
references
References 61 publications
12
162
0
Order By: Relevance
“…Following trypsinization and washing, cells were suspended in phenol red-free DMEM/ Matrigel (1:1, v/v). A syngeneic orthotopic mouse breast tumor model was established as before ( 13 ) were injected sub cutaneously into the fl ank. Expression of exogenous proteins was maintained by adding 2 mg/ml doxycycline to the drinking water.…”
Section: Mouse Tumor Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following trypsinization and washing, cells were suspended in phenol red-free DMEM/ Matrigel (1:1, v/v). A syngeneic orthotopic mouse breast tumor model was established as before ( 13 ) were injected sub cutaneously into the fl ank. Expression of exogenous proteins was maintained by adding 2 mg/ml doxycycline to the drinking water.…”
Section: Mouse Tumor Modelsmentioning
confidence: 99%
“…Expression of exogenous proteins was maintained by adding 2 mg/ml doxycycline to the drinking water. Tumor growth was monitored as before ( 13 ). To establish a metastatic model, 4T1 cells (1.5 × 10 5 , in PBS) were injected into BALB/c mice through the tail vein.…”
Section: Mouse Tumor Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth reduction is synergic with doxorubicin and the combined therapy decreases tumor growth by >70﹪ for about 17 days (Table 1). Subsequent lung and liver metastases were also reduced by about 50﹪-60﹪ with ATX inhibition [76,148] . In the same studies, we showed for first time that activation of LPA 1 receptors increases the stabilization of the transcription factor, Nrf2, and induces its nuclear translocation [148] .…”
Section: Atx Inhibitorsmentioning
confidence: 98%
“…It was the first reported ATX inhibitor to reduce plasma LPA levels in vivo for an extended period [140] . In rat air-pouch models, 30 mg/kg PF-8380 inhibited inflammatory hyperalgesia with the same efficacy as 30 mg/kg naproxen, a routinely used nonsteroidal anti-inflammatory drug Inflammatory hyperalgesia [140] Radiotherapy sensitizer in glioblastoma [146] ONO-8430506 Autotaxin activity inhibitor (competitive) Preclinical IC 50 5 nmol/L 10-30 mg/kg Benign prostatic hyperplasia [147] Reduces breast tumor growth and metastasis and increases sensitization to doxorubicin [76,148] Lpathomab TM LPA monoclonal antibody Preclinical 25 mg/kg Traumatic brain injury [127] AM966 LPA 1 antagonist Preclinical IC 50 17 nmol/L 10 mg/kg Idiopathic pulmonary fibrosis [132] BMS-986020 LPA 1 antagonist Phase II 600 mg/day (patients) Idiopathic pulmonary fibrosis [133] BMS-986202/AM152 LPA 1 antagonist Phase I 20-40 mg/kg Idiopathic pulmonary fibrosis [134] SAR100842 LPA 1/3 antagonist Phase II 20-40 mg/kg Systemic sclerosis [135] Gene overexpression Induced LPP gene expression Preclinical Overexpressed in cancer cells LPP3 overexpression reduces ovarian cancer cell growth [118] LPP1 overexpression reduces tumor growth and metastasis in breast and thyroid cancers [116] (NSAID) [140] . At this concentration, PF-8380 maximally reduced LPA levels in both plasma and at the site of inflammation.…”
Section: Atx Inhibitorsmentioning
confidence: 99%